2003
DOI: 10.1002/anie.200351921
|View full text |Cite
|
Sign up to set email alerts
|

Ligand and Metal Effects on the Formation of Main‐Group Polyhedral Clusters

Abstract: The reaction of AlMe3 or ZnMe2 with hppH (hppH=1,3,4,6,7,8‐hexahydro‐2H‐pyrimido[1,2‐a]pyrimidine) and then with tBuLi affords [Li8(H)m(hpp)6]n+[X]−n, X=[ZntBu3], m=n=1 (the cation core of which is shown); X=[Li(Me2AltBu2)2], m=0, n=2, as the major product in each case. These data reveal that non‐aromatic heterocycle hppH and ZnMe2 can be employed to generate novel hydride‐encapsulation main‐group‐metal clusters, and that related polylithium architectures can also incorporate a central void.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Hence, monomeric {4,6-tBu 2 C 6 H 4 -(CMe 2 CH 2 -2)BH(C 5 H 4 )}{CpMo(H) 2 }Li·TMEDA, [32] dimeric {(DMPE) 2 MoH(NO)·Et 3 BHLi} 2 (DMPE = bis(dimethylphosphanyl)ethane), [33] and polymeric {(DMPE) 2 -Mo(NO) 2 ·Et 3 BHLi} ϱ [34] all reveal B(µ-H)Li components, while (DMPE) 2 TaH 3 (µ-H) 2 ·Et 3 BHLi incorporates a core Ta(µ-H) 2 Li metallocycle linked to a B(µ-H)Li unit, [35] and {(DCHPB) 2 Ru(µ-H) 3 ·(s-Bu) 3 BHK} 2 {DCHPB = bis(dicyclohexylphosphanyl)butane} reveals both Ru(µ-H) 3 K and B(µ-H)K 2 motifs peripheral to a (KO) 2 core. [36] Core metallocycles of the type noted in (3) 2 and (4) 2 {that is K(µ-H) 2 K}, have been suggested previously only in the non-trivial 9-borafluorenyl "ate" dimer of 1-mesityl-5,7,9-trimethyl-9-hydro-9-borafluorenyl potassium that results from the reduction of 2,6-Mes 2 C 6 H 3 BBr 2 by KC 8 and also in the B-B-bonded diborate bis{1-(Trip-5,7-diisopropyl-9-hydro-9-borafluorenyl)}bis(potassium) that results from the comparable treatment of 2,6-Trip 2 C 6 H 3 BBr 2 . [21] In each of these two instances, the dimeric aggregates have been extensively supported by inter-monomer arene stabilization of the metal centers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, monomeric {4,6-tBu 2 C 6 H 4 -(CMe 2 CH 2 -2)BH(C 5 H 4 )}{CpMo(H) 2 }Li·TMEDA, [32] dimeric {(DMPE) 2 MoH(NO)·Et 3 BHLi} 2 (DMPE = bis(dimethylphosphanyl)ethane), [33] and polymeric {(DMPE) 2 -Mo(NO) 2 ·Et 3 BHLi} ϱ [34] all reveal B(µ-H)Li components, while (DMPE) 2 TaH 3 (µ-H) 2 ·Et 3 BHLi incorporates a core Ta(µ-H) 2 Li metallocycle linked to a B(µ-H)Li unit, [35] and {(DCHPB) 2 Ru(µ-H) 3 ·(s-Bu) 3 BHK} 2 {DCHPB = bis(dicyclohexylphosphanyl)butane} reveals both Ru(µ-H) 3 K and B(µ-H)K 2 motifs peripheral to a (KO) 2 core. [36] Core metallocycles of the type noted in (3) 2 and (4) 2 {that is K(µ-H) 2 K}, have been suggested previously only in the non-trivial 9-borafluorenyl "ate" dimer of 1-mesityl-5,7,9-trimethyl-9-hydro-9-borafluorenyl potassium that results from the reduction of 2,6-Mes 2 C 6 H 3 BBr 2 by KC 8 and also in the B-B-bonded diborate bis{1-(Trip-5,7-diisopropyl-9-hydro-9-borafluorenyl)}bis(potassium) that results from the comparable treatment of 2,6-Trip 2 C 6 H 3 BBr 2 . [21] In each of these two instances, the dimeric aggregates have been extensively supported by inter-monomer arene stabilization of the metal centers.…”
Section: Resultsmentioning
confidence: 99%
“…-[{PhN(2-C 5 H 4 N)} 6 -HLi 8 ] + , [5,6] X-ray analysis revealed encapsulation of the hydride center by a pseudocubic arrangement of alkali metal ions, each face of which was straddled by a bidentate amido ligand. The omission of lithium from the cluster has been noted, with the observation of neutral {PhN(2-C 5 H 4 N)} 6 HLi 7 and, of particular import in understanding the geometrical constraints of these systems, the use of hppH (= 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidine) [7] has recently allowed the comparison of [(hpp) 6 HLi 8 ] + with its hydride-free parent cluster [(hpp) 6 Li 8 ] 2+ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An X-ray crystal structure determination of the [t-Bu 3 Zn] − anion present in 21 62 has an almost perfect trigonal planar arrangement [Zn−C bond distances 2.080(7), 2.059(7) and 2.057(8)Å; C−Zn−C angles 118.1(2), 120.7(3) and 120.6 (3) • ]. Compound 21 was prepared by reacting 1,3,4,6,7,8-hexahydro-2H -pyrimido [1,2]pyrimidine, Me 2 Zn and tBuLi (equation 9).…”
Section: {[(Mementioning
confidence: 99%
“…doi:10.1016/j.jorganchem.2005.02.033 plane as the ÔCN 2 Õ amidine component in this molecule ensures a favourable alignment for overlap of the lone-pair with the empty p-orbital of the sp 2 -hybridised carbon. Previous work by ourselves and others have shown that the [hpp] À anion chelates to a range of different main group and transition metals [2], including lithium [3], aluminium [4], tin [5], zinc [6], yttrium [7] and titanium [8,9]. Crystallographic data for a series of mono-and bis-ligand compounds of titanium has indicated notably shorter Ti-N distances in [Ti(hpp)Cl 2 (l-Cl)] 2 and Ti(hpp) 2 Cl 2 when compared to the corresponding benzamidinate [10] and acyclic guanidinate [11] compounds.…”
Section: Introductionmentioning
confidence: 99%